Separation of charge carriers and generation of reactive oxygen species by TiO2 nanoparticles mixed with differently-coated gold nanorods under light irradiation. (3rd April 2019) - Zhang, Hui; Meng, Dejing; Fu, Bing; Fan, Huizhen; Cai, Rui; Fu, Peter P.; Wu, Xiaochun
Abstract: Combinations of semiconductor nanoparticles (NPs) with noble metal NPs enable an increase in the photoactivity of semiconductor NPs into the visible and near-infrared regions. The design rationale of the semiconductor-metal hybrid nanostructures for the optimization of charge carrier separation and reactive oxygen species (ROS) generation remains unclear. In this study, the interactions of Au nanorods (AuNRs) with TiO2 NPs were modulated by controlling their surface charges. Positively charged AuNRs formed aggregates with the negatively charged TiO2 NPs (AuNR@CTAB/TiO2 ) upon mixing, suggesting that Schottky junctions may exist between Au and TiO2 . In contrast, negatively charged AuNRs (AuNR@PSS) remained spatially separated from the TiO2 NPs in the mixed suspension (AuNR@PSS/TiO2 ), owing to electrostatic repulsion. We used electron spin resonance (ESR) spectroscopy to detect the separation of charged carriers and ROS generation in these two mixtures under simulated sunlight irradiation. We also explored the role of dissolved oxygen in charge carrier separation and ROS generation by continuously introducing oxygen into the AuNR@CTAB/TiO2 suspension under simulated sunlight irradiation. Moreover, the generation of ROS by the AuNR@CTAB/TiO2 and AuNR@PSS/TiO2 mixtures were also examined under 808 nm laser irradiation. Our results show that the photogenerated electrons of excited semiconductor NPs are readily transferred to noble metal NPs simply by collisions, but the transfer of photogenerated hot electrons from excited AuNRs to TiO2 NPs is more stringent and requires the formation of Schottky junctions. In addition, the introduction of oxygen is an efficient way to enhance the photocatalytic activity of semiconductor NPs/noble metal NPs system combinations.